Investigação das alterações citogenéticas em pacientes pediátricos com leucemia linfóide aguda do Rio Grande do Norte - Gil, Erica Aires (2011)
Leukemia is a heterogeneous group of hematologic malignancies that result from partial or total transformation of the blast cells. The Acute Lymphoblastic Leukemia (ALL) is the most common malignancy in childhood, especially in male, Caucasian children younger than 14 years. Several criteria are adopted to classify ALL, including the cell morphology, cytochemistry, immunophenotyping and cytogenetic analysis. Cytogenetic studies allow a more detailed analysis to detect chromosomal abnormalities of leukemic cells. These modifications will determine the diagnosis, classification, stage characterization, remission assessment and prognosis. In this study were evaluated 30 patients, aged from four months to seventeen years, of both sexes and various ethnicities. The age distribution showed that 67% of patients had between one and ten years (with mean age of XX years old), the most prevalent ethnic was Caucasian (50%) and 57% were males. According to immunophenotype, 93% of patients had B-cells progenitor ALL and 7% early lineage T. Considering the total studied population, the most frequent medical findings were lymphadenopathy (37%), hepatomegaly (77%) and splenomegaly (70%), where one patient could present more than one of these medical findings. Regarding the CBC, the majority of patients had hemoglobin below 10 g / dl (73%), leukocyte count less than 10.000/μL (60%) and platelet count below 150.000/μL (83%). Chromosomal abnormalities were observed in 64% of all patients, where hyperdiploidy was the most common numerical change (67%), followed by hypodiploid (33%). All these data are in agreement with the literature. Moreover, complexes structural and/or number changes not yet described in literature were observed, which indicated poor prognosis. Finally, we concluded that this study demonstrated the importance of cytogenetic study in the diagnosis and identification of prognostic factors in pediatric patients with ALL in Rio Grande do Norte. The results obtained in this study are extremely useful and emphasizes that surveys of this nature must be conducted more frequently in our state